Sustainable Intensification of Maize in the Industrial Revolution: Potential of Nitrifying Bacteria and Archaea - Ayiti, Oluwatobi Esther; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
Sustainable intensification is a means that proffer a solution to the increasing demand for food without degrading agricultural land. Maize is one of the most important crops in the industrial revolution era, there is a need for its sustainable intensification. This review discusses the role of maize in the industrial revolution, progress toward sustainable production, and the potential of nitrifying bacteria and archaea to achieve sustainable intensification. The era of the industrial revolution (IR) uses biotechnology which has proven to be the most environmentally friendly choice to improve crop yield and nutrients. Scientific research and the global economy have benefited from maize and maize products which are vast. Research on plant growth-promoting microorganisms is on the increase. One of the ways they carry out their function is by assisting in the cycling of geochemical, thus making nutrients available for plant growth. Nitrifying bacteria and archaea are the engineers of the nitrification process that produce nitrogen in forms accessible to plants. They have been identified in the rhizosphere of many crops, including maize, and have been used as biofertilizers. This study's findings could help in the development of microbial inoculum, which could be used to replace synthetic fertilizer and achieve sustainable intensification of maize production during the industrial revolution.